Association Between Smoking and Molecular Subtypes of Colorectal Cancer. Issue 4 (14th June 2021) - Wang, Xiaoliang; Amitay, Efrat; Harrison, Tabitha A; Banbury, Barbara L; Berndt, Sonja I; Brenner, Hermann; Buchanan, Daniel D; Campbell, Peter T; Cao, Yin; Chan, Andrew T; Chang-Claude, Jenny; Gallinger, Steven J; et al.
Abstract: Background: Smoking is associated with colorectal cancer (CRC) risk. Previous studies suggested this association may be restricted to certain molecular subtypes of CRC, but large-scale comprehensive analysis is lacking. Methods: A total of 9789 CRC cases and 11 231 controls of European ancestry from 11 observational studies were included. We harmonized smoking variables across studies and derived sex study–specific quartiles of pack-years of smoking for analysis. Four somatic colorectal tumor markers were assessed individually and in combination, including BRAF mutation, KRAS mutation, CpG island methylator phenotype (CIMP), and microsatellite instability (MSI) status. A multinomial logistic regression analysis was used to assess the association between smoking and risk of CRC subtypes by molecular characteristics, adjusting for age, sex, and study. All statistical tests were 2-sided and adjusted for Bonferroni correction. Results: Heavier smoking was associated with higher risk of CRC overall and stratified by individual markers ( P trend < .001). The associations differed statistically significantly between all molecular subtypes, which was the most statistically significant for CIMP and BRAF . Compared with never-smokers, smokers in the fourth quartile of pack-years had a 90% higher risk of CIMP-positive CRC (odds ratio = 1.90, 95% confidence interval = 1.60 to 2.26) but only 35% higher risk for CIMP-negative CRC (odds ratio = 1.35, 95% confidence interval = 1.22 to 1.49; P difference = 2.1 x 10 -6 ). The association was also stronger in tumors that were CIMP positive, MSI high, or KRAS wild type when combined ( P difference < .001). Conclusion: Smoking was associated with differential risk of CRC subtypes defined by molecular characteristics. Heavier smokers had particularly higher risk of CRC subtypes that were CIMP positive and MSI high in combination, suggesting that smoking may be involved in the development of colorectal tumors via the serrated pathway.